3 - Progress and Challenges in Implementing the Women, Peace and Security Agenda in the African Union’s Peace and Security Architecture - Hendricks, Cheryl (Africa Development, 2017)
This article provides an initial overview of the African Union’s progress and challenges in implementing the Women, Peace and Security (WPS) agenda in its peace and security architecture. It reviews implementation in relation to representation, programming and in peacekeeping. The article contends that the WPS agenda has strong roots in Africa and that progress has been made in relation to the development of frameworks, policies and strategies. Representation of women in the architecture has improved but the AU still has a long way to go to see this through at programmatic level (for example in peace negotiations and peace support operations). The programmes and activities implemented also appear to be rather ad hoc and attempts at quick-fix measurable exercises. The article argues that the WPS agenda has been narrowed to focus on the inclusion of women into peace and security institutions and processes without a deeper reflection of what their participation may mean for legitimizing post-conflict patriarchal and militarized orders.